Pelatihan membuat e-learning berbasis moodle bagi guru dan siswa SMP Negeri 1 Pallangga - Dyah Darma Andayani; Dyah Vitalocca; Mardiana Mardiana (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This community service activity aims to improvethe effectiveness and efficiency of learning through training inthe use of e-learning in learning. Therefore, the results of thistraining are expected to be able to (a) increase the knowledgeof teachers in SMP Negeri 1 Pallangga towards e-learning; (b)train teachers in using e-learning; (c) train teachers to managee-learning learning; (d) train students to use e-learning. Thisactivity was attended by 36 participants (teachers and students)who taught and studied at SMP Negeri 1 Pallangga. Thetraining was carried out using several methods, namely:lectures, discussion/question and answer, practices anddemonstrations. Based on the results of the evaluation carriedout during the activity, both when presenting theoreticalmaterial and training on the use of e-learning, show thefollowing. (1) the activeness of participants in participating intraining materials is quite high; (2) participants have highmotivation and enthusiasm in implementing learning using elearning;(3) the average absorption of material mastery byparticipants is good and around 80% can use moodle elearning;(4) The supporting factors in the implementation ofthis training are that the participants have strong interest anddesire to use e-learning in classroom learning activities,students involved have a great motivation to use e-learning inlearning, while other inhibiting factors are limited facilities(network and limited laptop/computer devices) as well asseveral weak teachers in computer literacy. To be able to keepup with technological progress and the times, teachers shouldalways increase technology insight through the use of IT inlearning. So that in addition to having an impact on theefficiency and effectiveness of classroom learning, studentswill also have complete soft skills to always be integrated withtheir times.